A Field Study on Efficacy of Albendazole (Albezol®) Against Gastro-intestinal Nematodes in Ruminants - Theera Rukkwamsuk; Anawat Sangmalee; Korawich Anukoolwuttipong; Nitis Sookhong (Agriculture and Natural Resources, 2005)
A field study was aimed to determine efficacy of albendazole against gastro-intestinal nematodes in ruminants. Forty-eight infested animals (27 beef cattle and 21 goats) were used. Albendazole [Albezol®, 11.25% (wt/vol)] was given orally to animals at a dosage of 10 mg/kg body weight. Blood samples were collected at 0, 28 and 56 days after treatment for determination of packed cell volume (PCV) and plasma protein (PP) concentrations. Fecal samples were collected at 0, 7, 28, and 56 days after treatment and were examined for worm eggs using simple floatation method. When available, egg-containing fecal samples were counted for the number of eggs per gram (EPG) of feces using Mc Master technique. For beef cattle, the average (min, max) EPGs in fecal samples were 144 (100, 600), 0 (0, 0), 0 (0, 0) and 4 (0, 100) at day 0, 7, 28, and 56 days after treatment, respectively. Average percentages of beef cattle infested with GI-nematodes were 100, 0, 0, and 4 at day 0, 7, 28, and 56 days after treatment, respectively. Mean PCV (± SD) was 32.2 (± 4.2) % at day 0, the means were higher at 28 and 56 days after treatment. Compared with day 0, mean PP concentration was also higher at 28 days after treatment. For goats, average percentages of goats infested with GI-nematodes were 100, 0, and 14 at day 0, 7, and 28 after treatment, respectively. Average (min, max) numbers of eggs counted on 5 microscopic fields (40X) were 10 (1, 30), 0 (0, 0), and 1 (1, 2) at day 0, 7, and 28 after treatment. Mean PCV at day 28 after treatment was 31.6 (± 4.1)% and was higher than mean at day 0, 24.1 (± 5.2)%. Mean PP concentrations did not differ between day 0 and day 28 after treatment. Results showed high efficacy of albendazole in treatment and control of gastro-intestinal nematodes of ruminants.